2013
DOI: 10.1163/1937240x-00002195
|View full text |Cite
|
Sign up to set email alerts
|

Neodiaptomus prateek n. sp., a new freshwater copepod from Assam, India, with critical review of generic assignment of Neodiaptomus spp. and a note on diaptomid species richness (Calanoida: Diaptomidae)

Abstract: A B S T R A C TNeodiaptomus prateek n. sp. is described based on a plankton sample collected from Deepor Beel, a floodplain lake in the north-eastern, Indian state of Assam, which falls within the key biodiversity area of the Indo-Burma Hotspot. The new species fulfils all the principal criteria of the genus Neodiaptomus Kiefer, 1932, as revised by Kiefer (1939). It has, however, a spectacular autapomorphic feature, which is perhaps unparalleled in Diaptomidae as a whole -a massive coxal plate ending in a thum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Neodiaptomus schmackeri (Poppe and Richard, 1892) (Figure 8C) was originally described as Diaptomus schmackeri [61]. Among the 14 reported species of the genus Neodiaptomus [62], N. schmackeri is the most widely distributed species, being reported from southern China, the Russian Far East, Nepal, India, Bangladesh, Sri Lanka, Korea, Japan, Taiwan, the Philippines, Malaysia, Singapore [1,63] and Vietnam [32]. Recently, Alfonso et al (2014) [64] have reported this species in eight lakes in Albania (Europe) for the first time.…”
Section: Genus Neodiaptomus Kiefer 1932mentioning
confidence: 99%
“…Neodiaptomus schmackeri (Poppe and Richard, 1892) (Figure 8C) was originally described as Diaptomus schmackeri [61]. Among the 14 reported species of the genus Neodiaptomus [62], N. schmackeri is the most widely distributed species, being reported from southern China, the Russian Far East, Nepal, India, Bangladesh, Sri Lanka, Korea, Japan, Taiwan, the Philippines, Malaysia, Singapore [1,63] and Vietnam [32]. Recently, Alfonso et al (2014) [64] have reported this species in eight lakes in Albania (Europe) for the first time.…”
Section: Genus Neodiaptomus Kiefer 1932mentioning
confidence: 99%
“…Nevertheless, the Indian literature still lacks attention on regional faunal diversity of these `wheel animalcules' except for NEIthe most rich and Rotifera biodiverse region of India (Sharma & Sharma 2014a. Importantly, Assam state of NEI, a part of the Indo-Myanmar biodiversity hotspot, merits attention as `the Assam-gateway' which is recognized as a unique phase in the biogeographic evolution of India (Mani 1974, Ranga Reddy 2013. Further, this state is characterized by the fluvial floodplain wetlands of the Brahmaputra and Barak Rivers; the former are hypothesized as globally rich rotifer habitats (Sharma & Sharma 2008, 2014b, Sharma et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently there are several reports on zooplankton studies from different parts of India that includes the studies on zooplankton composition in the limnetic zones of two subtropical lakes, Nainital and the Bhimtal of Uttar Pradesh, India (21) . Investigations on rotifer, cladocera and copepoda group has been carried out from eastern, North West and North East part of India (22)(23)(24)(25)(26) . Zooplankton emergence pattern and resting egg diversity of dried water bodies in north Maharashtra (27) .…”
Section: Introductionmentioning
confidence: 99%